Uniwersalność instytucji rodziny i kierunku je j przemian - Kwak, Anna (Wydawnictwo Naukowe UAM, 2002)
Family is the organization existing universally but differentiated in its forms. Family is both a social group and social institution. Social change and social conditions have a great influence on family. Such factors as culture, religion, political system and level of economic development have an important impact on the speed of change in family structure and organization. However, some general trends have a world-wide character and cause universal transformation in family life.
Universality of the family institution and direction of its transformation